Potty Super Team - Jones , Wednesday; Schmidt , Anita (Autumn Publishing, Cottage Farm, England, 2022, 2022)
Even superheroes use the potty! Join The Amazing Ava and The Marvelous Max on his most urgent mission yet, and help your little superhero develop essential potty skills, from avoiding accidents to washing hands
English stories
Keywords: Fiction; picture books